Malaysian Muslim Knowledge And Compliance With The Rule Of Distancing Prayers By One Meter During The Covid-19 Pandemic - Irwan Mohd Subri; Muhamad Firdaus Ab Rahman; Hamza Abed Al-Karim Hammad; Hasanah Abd Khafidz; Mohd Hapiz Mahaiyadin; Arieff Salleh Rosman; Aqeel Khan (Centivens Institute of Innovative Research, 2024)
Non-Indexed Publication